Explaining the Magnitude of Liquidity Premia: The Roles of Return Predictability, Wealth Shocks, and State‐Dependent Transaction Costs - LYNCH, ANTHONY W.; TAN, SINAN (Journal of Finance, 2011)
ABSTRACT Constantinides (1986) documents how the impact of transaction costs on per‐annum liquidity premia in the standard dynamic allocation problem with i.i.d. returns is an order of magnitude smaller than the cost rate itself. Recent papers form portfolios sorted on liquidity measures and find spreads in expected per‐annum return that are the same order of magnitude as the transaction cost spread. When we allow returns to be predictable and introduce wealth shocks calibrated to labor income, transaction costs are able to produce per‐annum liquidity premia that are the same order of magnitude as the transaction cost spread.